HIFI: Explaining and Mitigating Algorithmic Bias Through the Lens of Game-Theoretic Interactions - Zhang, Lingfeng; Wang, Zhaohui; Zhang, Yueling; Zhang, Min; Wang, Jiangtao (Proceedings / International Conference on Software Engineering, 2025)
Machine Learning (ML) algorithms are increasingly used in decision-making process across various social-critical domains, but they often somewhat inherit and amplify bias from their training data, leading to unfair and unethical outcomes. This issue highlights the urgent need for effective methods to detect, explain, and mitigate bias to ensure the fairness of ML systems. Previous studies are prone to analyze the root causes of algorithmic bias from a statistical perspective. However, to the best of our knowledge, none of them has discussed how sensitive information inducing the final discriminatory decision is encoded by ML models. In this work, we attempt to explain and mitigate algorithmic bias from a game-theoretic view. We mathematically decode an essential and common component of sensitive information implicitly defined by various fairness metrics with Harsanyi interactions, and on this basis, we propose an in-processing method HIFI for bias mitigation. We conduct an extensive evaluation of HIFI with 11 state-of-the-art methods, 5 real-world datasets, 4 fairness criteria, and 5 ML performance metrics, while also considering intersectional fairness for multiple protected attributes. The results show that HIFI surpasses state-of-the-art in-processing methods in terms of fairness improvement and fairness-performance trade-off, and also achieves notable effectiveness in reducing violations of individual fairness simultaneously.